IMPLEMENTATION OF THINKING DESIGN FOR OPTIMIZING THE UI/UX OF THE ORDERING CHATBOT AT WARUNG PEMPEK MANG HANIF: IMPLEMENTATION OF THINKING DESIGN FOR OPTIMIZING THE UI/UX OF THE ORDERING CHATBOT AT WARUNG PEMPEK MANG HANIF - kartina, Riza; Arif Fadillah; Rudiansyah (IKesT Muhammadiyah Palembang, 2025)
In the ever-growing digital era, Warung Pempek Mang Hanif faces challenges in managing an increasingly complex ordering process due to the increasing number of customers. The current manual ordering system has limitations such as recording errors, delays, and customer dissatisfaction. This research aims to optimize the UI/UX of an ordering chatbot by applying a Design Thinking approach. Design Thinking methodology is applied to understand user needs and preferences, design innovative solutions, and ensure optimal user experience. Chatbot development was carried out using the Eclipse IDE and the Java programming language, focusing on main features such as order acceptance, menu information and order status. This research shows that the application of Design Thinking can produce responsive, intuitive and efficient chatbots, thereby increasing customer satisfaction and reducing staff workload.